ANALISIS KEBUTUHAN RAK PENYIMPANAN DOKUMEN REKAM MEDIS AKTIF DI PUSKESMAS KENDALKEREP MALANG - Prima Soultoni Akbar; Tsalits Maulidah Hariez (program studi Rekam Medis dan Infomasi Kesehatan ITSK RS dr Soepraoen Malang, 2023)
Medical record should be kept in store shelves that kept confidential, to avoid damage and officers in the medical record and return.So that this be effective and efficient store needs planning needs to be sufficient to keep within a certain period of time to the time will come and facilitate the back by officers.in storage of Puskesmas Kendalkerep record, not optimal because there are still kept are right on top in addition to store shelves triggered by the lack of store shelves so that it difficult to find the medical record can slow the documents and the medical record not yet destroyed had to be destroyed.Puskesmas kendalkerep also have not just calculate the store shelves. The research is descriptive qualitative research, observing and analyzing the documents record store shelves puskesmas kendalkerep.The way the collection of data using observation and interview.The observation is made by means of observing, noted, and measuring the amount of patient visits, the thickness of the medical record, size store shelves and calculate the store shelves with watson and trend analysis method.The number of active medical record store shelves documents required to 5 years woultd go to 9 unit so it needs additional 4 shelf unit